Cyclin-dependent kinase (CDK) 9 and 4/6 inhibitors in acute myeloid leukemia (AML): a promising therapeutic approach. (2nd November 2019) - Lee, Daniel J.; Zeidner, Joshua F.
ABSTRACT: Introduction : Despite advancements over the last 2 years, outcomes for acute myeloid leukemia (AML) are poor; however, a greater comprehension of disease mechanisms has driven the investigation of new targeted treatments. Cyclin-dependent kinases (CDKs) regulate cell cycle progression, transcription and DNA repair, and are aberrantly expressed in AML. Targeting the CDK pathway is an emerging promising therapeutic strategy in AML. Areas covered: We describe the rationale for targeting CDK9 and CDK4/6, the ongoing preclinical and clinical trials and the potential of these inhibitors in AML. Our analysis included an extensive literature search via the Pubmed database and clinicaltrials.gov (March to August, 2019). Expert opinion : While CDK4/6 inhibitors are early in development for AML, CDK9 inhibition with alvocidib has encouraging clinical activity in newly diagnosed and relapsed/refractory AML. Preclinical data suggests that leukemic MCL-1 dependence may predict response to alvocidib. Moreover, MCL-1 plays a key role in resistance to BCL-2 inhibition with venetoclax. Investigational strategies of concomitant BCL-2 and CDK9 inhibition represent a promising therapeutic platform for AML. Furthermore, preclinical data suggests that CDK4/6 inhibition has selective activity in patients with KMT2A- rearrangements and FLT3 mutations. Incorporation of CDK9 and 4/6 inhibitors into the existing therapeutic armamentarium may improve outcomes in AML.